Effect of different genotypes of Tithonia diversifolia on fermentation of feed mixtures with Urochloa brizantha cv. Marandú - Arango, Jacobo; Rivera, Julian; Chará, Julián; Barahona Rosales, Rolando (Commonwealth Scientific and Industrial Research Organisation, 2021)
Tithonia diversifolia (Mexican sunflower) is a shrub used for animal feed that has outstanding agronomic and chemical characteristics. Its potential to modify the dynamics of fermentation and improve the supply of nutrients to ruminants has received considerable attention. This study was designed to determine the effect of different genotypes of T. diversifolia on ruminal fermentation and degradation of dry matter (DM), concentration of volatile fatty acids, and production of methane (CH4) when mixed with a low-quality tropical grass, Urochloa brizantha (palisade grass). In a randomised complete block design, mixtures of seven genotypes of T. diversifolia with U. brizantha cv. Marandú were evaluated by using the in vitro gas production technique. The effect of fertilisation was also evaluated for each genotype. Inclusion of T. diversifolia significantly (P < 0.05) increased the supply of nutrients and modified fermentation parameters. DM degradation of biomass after 72 h was greater in the presence of T. diversifolia than for feeds based only on U. brizantha (68.0% vs 63.4%; P < 0.01). CH4 production was lower (P < 0.05) during fermentation with some T. diversifolia genotypes (25.3 vs 27.7 mg CH4 g–1 incubated DM), and the acetic:propionic acid ratio was also lower. Fertilisation of T. diversifolia genotypes increased DM degradation, increased the content of certain nutrients (e.g. crude protein) and modified CH4 production. Therefore, inclusion of T. diversifolia in mixtures based on low-quality tropical grasses such as U. brizantha increases the supply of nutrients (crude protein, minerals, energy) and can modify the products of enteric fermentation, with some genotypes decreasing enteric CH4 emissions.